"Skip, it's violent": An index to measure violent entertainment addiction and aggressive behavior among adolescents / Ana Afrina Abd Jamil, Yarina Ahmad and Ahmad Naqiyuddin Bakar - Abd Jamil, Ana Afrina; Ahmad, Yarina; Bakar, Ahmad Naqiyuddin (2021)
The "Skip, it's violent" index is an indicator to measure violent entertainment addiction and aggressive behaviour among adolescents. This index covers five dimensions: self-motivation, parental monitoring, peer influence, addiction, and aggressive behaviour. The items for each dimension are developed through a thorough literature review. This product is targeted at adolescents, government, and educational institutions as the end-user to receive its benefits. The index is essential to measure the current status of violent entertainment addiction and aggressive behaviour among adolescents in Malaysia. Further, this index is vital in addressing criminal acts and other social problems among adolescents whilst ensuring children's social development and well-beingness.